"I went behind the workers singing": poetry, history and revolution in Todos bailan by Raúl González Tuñón (Anclajes, 2011)
In 1935, Raúl González Tuñón published Todos bailan, a collection of poems that accounts for a new writer’s image, which the author built up in his texts. Although many aspects of such an image were already present in his previous books, his affiliation to the Communist Party in 1934 and the role of intellectual he assumed when expressing his opinion about current political affairs in diverse newspapers and magazines, expose a new thinking of poetry in accordance with revolutionary essentials and a new writer’s image related to a moral conception of writing.
Keywords: Raúl González Tuñón; Todos bailan; image of writer; revolution; function of poetry